Nonlinear mitigation using carrier phase estimation and digital backward propagation in coherent QAM transmission. - Lin, Chien-Yu; Asif, Rameez; Holtmannspötter, Michael; Schmauß, Bernhard (Optics Express, 2012)
We investigate the performance of carrier phase estimation (CPE) and digital backward propagation (DBP) in compensating fiber nonlinearity for 224 Gbps polarization-multiplexed quadrature-amplitude-modulation coherent systems with level of 4 and 16 (PM-4-QAM and PM-16-QAM) over standard single-mode fiber (SSMF) uncompensated link. The results from numerical simulation show the individual performance of CPE and DBP as well as their mutual influence. With DBP compensation, required CPE tap number for optimal performance can be reduced by 50% for 4-QAM signal and 67% for 16-QAM signal compared to linear compensation. On the other hand, employing CPE compensation after DBP also allows to reduce DBP steps. In the mentioned PM-16-QAM system, 60% reduction in the required number of DBP steps to achieve BER=10(-3) is possible, with a step-size of 200 km, which reveals great potential to reduce the complexity for future real time implementation.